Vladik Nersesiantz`s Life and Scientific Activity (1938-2005 - Amiryan , K. (Bulletin of Yerevan University C: Jurisprudence, 2018)
The great scientist VladikNersesiantz`slife and scientific activity are discussed in the article presented. The article reveals the interesting facts from his childhood, periods of study and scientific work. The author analyses Nersesiantz`s main scientific works and their content. The article also presents some thoughts of Nersesiantz, as well as thoughts of others about him.